Negative active material and preparation method thereof, negative pole piece, secondary battery and electric device
By setting a silicon material layer on the surface of the MXENE 3D material, a composite negative active material is formed, the electrode structure destruction and circulation performance of the volume of the silicon material in the lithium -ion battery in the lithium ion battery are solved, and the cycle stability of the high magnification and the rapid charging conditions is achieved Increased sex and energy density.
Patent Information
- Application Number
- CN202310923643.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-07-26
AI Technical Summary
The theoretical specific capacity of commercial graphite anode materials of existing lithium-ion batteries is low, which cannot meet the needs of high capacity and high power. At the same time, silicon as a substitute material changes in the volume of lithium-ion embedding and disengagement, resulting in electrode structure failure and Cyclic performance deteriorates.
The MXENE three -dimensional material with a three -dimensional network skeleton is used as the basis of the negative active material, and the silicon material layer is set on its surface to form a composite material. MXENE materials have high -electronic conductors and fast lithium ion transmission characteristics. The silicon material layer shortens the transmission path of lithium ions, enhances the magnification performance of the negative electrode, and changes through the volume of the volume of the three -dimensional network skeleton buffer silicon.
It improves the cycle stability of lithium -ion batteries under the rapid charging and discharge conditions of high magnification, enhances the magnification performance and energy density of the negative electrode, reduces the expansion rate, and extends the service life of the battery.
Smart Images

Figure CN119381413A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a negative electrode active material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, especially with the widespread application of lithium-ion batteries in new energy electric vehicles, higher requirements have been put forward for the energy density and fast charging capability of lithium-ion batteries. However, the theoretical specific capacity of commercial graphite anode materials is only 372mAh / g, which is relatively low and can no longer meet the growing demand for high capacity and high power. Therefore, finding higher capacity electrode materials to replace commercial graphite anodes has become an important exploration direction for lithium-ion battery anode research.
[0003] Silicon is the material with the highest known lithium insertion capacity (3579-4200mAh / g). It also has the advantages of low discharge potential and abundant natural reserves, making it the most promising negative electrode material for lithium-ion batteries to replace graphite. However, during the process of lithium ion insertion and extraction, silicon materials will have a volume change of up to 300%, which will lead to problems such as electrode structure destruction, electrical connection failure, and continuous consumption of active materials, and ultimately lead to the destruction of battery performance, such as deterioration of cycle performance. Improving the volume change problem of silicon during battery cycles through nano-scaling or silicon-carbon composites is currently a relatively common method, but the improvement effect is not ideal, especially the cycle stability problem under high-rate rapid charge and discharge conditions cannot be effectively solved. Therefore, the existing negative electrode active materials still need to be improved. Summary of the invention
[0004] Based on this, it is necessary to provide a negative electrode active material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device to improve the cycle stability of the battery under high-rate rapid charge and discharge conditions.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a negative electrode active material, comprising: a MXene three-dimensional material having a three-dimensional network skeleton and a silicon material layer arranged on at least a portion of the surface of the MXene three-dimensional material, wherein the MXene three-dimensional material comprises a MXene material, and the general structural formula of the MXene material is Mn+1Xn, wherein M comprises at least one of Ti, Nb, V, Mo, Zr, Cr, W and Ta; X comprises at least one of C and N; and n is 1, 2 or 3.
[0006] The above-mentioned negative electrode active material includes a MXene three-dimensional material and a silicon material layer arranged on the surface of the MXene three-dimensional material, wherein the MXene three-dimensional material has a three-dimensional network skeleton, which provides a buffer space for the volume change of silicon and reduces the expansion rate of the negative electrode. In addition, the MXene material, which is the main component of the MXene three-dimensional material, has the characteristics of high electronic conductivity and fast lithium ion transmission. The silicon material is arranged on the surface of the MXene three-dimensional material, which can shorten the transmission path of lithium ions and promote the rapid transmission of lithium ions, thereby improving the rate performance of the negative electrode. At the same time, the three-dimensional network skeleton of the MXene three-dimensional material forms a three-dimensional conductive network, which can also solve the problem of low conductivity of the silicon material itself and improve the cycle stability of the battery under high-rate rapid charging and discharging conditions.
[0007] In some of these embodiments, the MXene includes one or more of Ti2C and Ti3C2.
[0008] In some embodiments, the MXene material satisfies at least one of the following features (1) to (3):
[0009] (1) The diameter of MXene flakes is 2 to 10 μm;
[0010] (2) The number of MXene layers ranges from 1 to 5;
[0011] (3) The thickness of MXene flakes is 1nm to 10nm.
[0012] In some embodiments, the MXene three-dimensional material satisfies at least one of the following features (4) to (5):
[0013] (4) The mesoporosity of MXene three-dimensional materials is 30% to 70%;
[0014] (5) The density of MXene three-dimensional materials is 10 mg / cm 3 ~60mg / cm 3 .
[0015] In some of these embodiments, the MXene three-dimensional material is a MXene aerogel;
[0016] Optionally, the MXene aerogel further comprises graphene;
[0017] Optionally, based on the total mass of the MXene aerogel, the mass content of the graphene is 3% to 70%, and further optionally 20% to 60%.
[0018] In some of the embodiments, the thickness of the silicon material layer is 5 nm to 100 nm, and can be optionally 10 nm to 80 nm.
[0019] In some of the embodiments, the average volume particle size Dv50 of the silicon material in the silicon material layer is 2 nm to 30 nm, and can be optionally 3 nm to 10 nm.
[0020] In some of the embodiments, the silicon material layer is connected to at least a portion of the surface of the MXene three-dimensional material through chemical bonds. Optionally, active carbon sites are formed on the surface of the MXene three-dimensional material, and the silicon material layer is connected to at least a portion of the surface of the MXene three-dimensional material by bonding to the active carbon sites.
[0021] In some embodiments, the negative electrode active material satisfies at least one of the following characteristics (6) to (9):
[0022] (6) The average volume particle size Dv50 is 5 μm to 20 μm;
[0023] (7) Specific surface area is 1m 2 / g~30m 2 / g;
[0024] (8) Based on the mass of the negative electrode active material, the mass content of silicon is 1% to 70%;
[0025] (9) Based on the mass of the negative electrode active material, the mass content of the MXene material is 30% to 99%.
[0026] The second aspect of the present application provides a method for preparing the negative electrode active material, comprising:
[0027] Providing the MXene three-dimensional material;
[0028] The silicon material layer is formed on the MXene three-dimensional material.
[0029] In some embodiments, the method for preparing the MXene three-dimensional material comprises the following steps:
[0030] S11, mixing the MXene material, graphene oxide, a dispersant and a reducing agent to obtain a mixed solution;
[0031] S12, subjecting the mixed solution to a hydrothermal reaction to obtain a MXene gel;
[0032] S13, freeze-drying the MXene gel to obtain a MXene three-dimensional material.
[0033] In some embodiments, step S11 further comprises: adding a second etchant to the mixed solution to etch and form the active carbon sites, and optionally, the etchant is Ni 2+ Salt.
[0034] In some embodiments, the weight ratio of the second etchant to the MXene material is 0.05 to 0.3.
[0035] In some of the embodiments, the method for forming the silicon material layer includes at least one of chemical vapor deposition, physical vapor deposition, plasma spraying and screen printing, and chemical vapor deposition can be selected.
[0036] The third aspect of the present application provides a negative electrode plate, comprising the negative electrode active material of the first aspect of the present application or the negative electrode active material prepared by the method of the second aspect of the present application.
[0037] The fourth aspect of the present application provides a secondary battery, comprising the negative electrode plate of the third aspect of the present application.
[0038] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application.
[0039] Effects of the Invention
[0040] The negative electrode active material provided in the present application includes a MXene three-dimensional material and a silicon material layer arranged on the surface of the MXene three-dimensional material, wherein the MXene three-dimensional material has a three-dimensional network skeleton, which provides a buffer space for the volume change of silicon and reduces the expansion rate of the negative electrode. In addition, the MXene material, which is the main component of the MXene three-dimensional material, has the characteristics of high electronic conductivity and fast lithium ion transmission. The silicon material is arranged on the surface of the MXene three-dimensional material, which can shorten the transmission path of lithium ions and promote the rapid transmission of lithium ions, thereby improving the rate performance of the negative electrode. At the same time, the three-dimensional network skeleton of the MXene three-dimensional material forms a three-dimensional conductive network, which can also solve the problem of low conductivity of the silicon material itself and improve the cycle stability of the battery under high-rate rapid charging and discharging conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0042] Figure 2 for Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0043] Figure 3 It is a schematic diagram of a battery module according to one embodiment of the present application.
[0044] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.
[0045] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0046] Figure 6 FIG. 1 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0047] Description of reference numerals:
[0048] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION
[0049] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0050] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0055] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0056] The term "aerogel" refers to a lightweight solid material in which nano-colloidal particles aggregate to form a nano-skeleton and a nano-porous three-dimensional network skeleton, and the pores are filled with a gaseous dispersion medium. "Aerogel" generally refers to a nano-scale porous solid material formed by a sol-gel method, in which a certain drying method is used to replace the liquid phase in the gel with gas. It should be noted that in the internal structure of the aerogel, the pore size is relatively more uniform, with mesopores of 2 to 50 nm, and most of the pores in the aerogel are interconnected. The most notable feature of "aerogel" is its low density, and it is even called the world's lowest density solid.
[0057] At present, in order to meet market demand, the energy density of secondary batteries represented by lithium-ion batteries is getting higher and higher. With the continuous development of new energy electric vehicles, problems such as mileage anxiety and long charging time have become prominent. In this case, the improvement of the fast charging ability of high-energy-density batteries has become the focus of the development of the next generation of batteries. At the same time, in order to improve the energy density, silicon-based materials have been introduced in the selection of active materials for secondary batteries. Silicon-based materials will expand in volume during the cycle of secondary batteries. At the same time, silicon is a semiconductor with low conductivity and poor high-power discharge performance. During high-rate fast charging, the volume change of silicon-based materials is greater, which can exceed 300%, resulting in the destruction of the negative electrode conductive network. In order to solve the problem of volume change of silicon negative electrode materials, the existing technology focuses on the research of developing suitable carriers. However, based on the increasingly stringent demand for the fast charging ability of batteries, the inventors found that only the carrier to ensure the expansion space of silicon has limited improvement in the high-rate fast charging ability of negative electrode materials, and shortening the lithium ion transmission path can enable the anode to have the ability to quickly transmit lithium ions, thereby greatly improving its fast charging ability. Therefore, it is necessary to construct a negative electrode active material that can provide sufficient space to accommodate the volume change of silicon material and shorten the lithium ion transmission path, so as to solve the problem of cycle stability of high energy density batteries under high-rate rapid charging and discharging conditions.
[0058] Negative electrode active material
[0059] To this end, a first aspect of an embodiment of the present application provides a negative electrode active material, including a MXene three-dimensional material having a three-dimensional network skeleton and a silicon material layer disposed on at least a portion of the surface of the MXene three-dimensional material, wherein the MXene three-dimensional material includes a MXene material, and the structural formula of the MXene material is M n+1 X n , wherein M includes at least one of Ti, Nb, V, Mo, Zr, Cr, W and Ta; X includes at least one of C and N; and n is 1, 2 or 3.
[0060] In an embodiment of the present application, the negative electrode active material includes a MXene three-dimensional material and a silicon material layer arranged on the surface of the MXene three-dimensional material, wherein the MXene three-dimensional material has a three-dimensional network skeleton, which provides a buffer space for the volume change of silicon and reduces the expansion rate of the negative electrode. In addition, the MXene material, which is the main component of the MXene three-dimensional material, has the characteristics of high electronic conductivity and fast lithium ion transmission. The silicon material is arranged on the surface of the MXene three-dimensional material, which can shorten the transmission path of lithium ions and promote the rapid transmission of lithium ions, thereby improving the rate performance of the negative electrode. At the same time, the three-dimensional network skeleton of the MXene three-dimensional material forms a three-dimensional conductive network, which can also solve the problem of low conductivity of the silicon material itself and improve the cycle stability of the battery under high-rate rapid charging and discharging conditions.
[0061] It should be noted that the silicon material layer can be provided on part of the surface of the MXene three-dimensional material, or on the entire surface of the MXene three-dimensional material; preferably, the silicon material layer is provided on the entire surface of the MXene three-dimensional material, for example, the silicon material layer covers the three-dimensional network skeleton of the MXene three-dimensional material, and the three-dimensional network skeleton of the MXene three-dimensional material is completely covered with the silicon material layer. Furthermore, the surface formed by the silicon material layer can be a continuous surface or a discontinuous surface; preferably, the surface formed by the silicon material layer is a continuous surface.
[0062] In some embodiments, the MXene material includes one or more of Ti2C and Ti3C2.
[0063] The above-mentioned MXene materials are inevitably surface functionalized during the preparation process, so the surface usually also includes one or more surface functional groups (also known as end-capping groups). In some embodiments, the surface functional groups of the MXene material include at least one of hydroxyl, halogen and oxygen-containing functional groups. It should be noted that the surface functional groups of the MXene material are usually naturally formed during the preparation process, but specific surface functional groups can also be generated through chemical treatment, thermal annealing and mechanical exfoliation processes. Depending on the surface functional groups, the MXene material may include but is not limited to one or more of oxides, epoxides, hydroxides, alkoxides with 1 to 5 carbon atoms, fluorides, chlorides, bromides or iodides. In some specific embodiments, the surface functional groups of the MXene material include F, O and OH.
[0064] The MXene material in MXene three-dimensional materials is a two-dimensional lamellar structure, and a three-dimensional network skeleton is formed by stacking multiple two-dimensional lamellar structures.
[0065] In some embodiments, the lamella diameter of the MXene material is 2 μm to 10 μm. The larger the lamella diameter of the MXene material, the more active sites there are, which is more conducive to the transfer of charges. The lamella diameter has better structural stability and charge transfer capability within this range. As an example, the lamella diameter of the MXene material can be, but is not limited to, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and any value therebetween.
[0066] In some embodiments, the number of MXene material layers is 1 to 5, such as 2, 3, 4, and any value therebetween. When the number of MXene material layers is within the above range, the specific surface area is larger, the active sites are more, and the electronic conductivity is better.
[0067] In some embodiments, the MXene material has a sheet thickness of 1 nm to 10 nm, such as 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 9.5 nm, and any value therebetween. When the sheet thickness of the MXene material is within the above range, the material conductivity and structural stability are better. Further optionally, the sheet thickness of the MXene material is 1 nm to 4.5 nm.
[0068] In some embodiments, the mesoporosity of the MXene three-dimensional material is 30% to 70%, for example 35%, 40%, 45%, 50%, 55%, 60%, 65% and any value therebetween. The mesoporosity of the MXene three-dimensional material is within the above range, the specific surface area is higher, more silicon materials can be arranged with it, the negative electrode active material has a higher silicon content, has a higher energy density, and has better structural stability. Optionally, the mesoporosity of the MXene three-dimensional material is 40% to 60%. It should be noted that the mesoporosity of the MXene three-dimensional material refers to the porosity of the mesopores with a pore size of less than 50nm in the MXene three-dimensional material.
[0069] In some embodiments, the density of the MXene three-dimensional material is 10 mg / cm 3 ~60mg / cm 3 By optimizing the density of MXene three-dimensional materials, the negative electrode active material can have a higher weight-to-capacity ratio, which can further improve the overall energy density of the battery.
[0070] In some embodiments, the MXene three-dimensional material is a MXene aerogel. MXene aerogel has a three-dimensional network skeleton, a larger specific surface area, a higher porosity, a lower density, a lighter material, and a stronger compressive resistance. It can greatly shorten the transmission path of lithium ions, further improve the rate performance, and effectively reduce the negative electrode expansion rate. Moreover, due to its extremely low density, compounding it with silicon materials can make the negative electrode active material have a higher weight-to-capacity ratio, which can further improve the overall energy density of the battery.
[0071] In addition to the MXene material, the MXene aerogel mentioned above may also include other two-dimensional lamellar materials to further improve the structural stability of the MXene aerogel, such as graphene, hexagonal boron nitride, molybdenum disulfide, tungsten diselenide, molybdenum diselenide, tungsten disulfide, platinum diselenide, molybdenum ditelluride, tungsten ditelluride, vanadium diselenide, chromium disulfide, chromium diselenide, transition metal dichalcogenides, black phosphorus and combinations thereof, without specific limitation. It should be noted that the lamella diameter, number of lamellae and lamella thickness of other two-dimensional lamellar materials need to match the lamella diameter, number of lamellae and lamella thickness of the MXene material to form a structurally stable aerogel, which can be selected according to actual needs.
[0072] In some embodiments, the MXene aerogel includes a MXene material and graphene. Optionally, based on the total mass of the MXene aerogel, the mass content of graphene is 3% to 70%, such as 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% and any value therebetween. The mass content of graphene in the MXene aerogel is within the above range, the MXene aerogel structure is more stable, and the electronic conductivity and lithium ion transmission rate are better. Optionally, based on the total mass of the MXene aerogel, the mass content of graphene is 20% to 60%.
[0073] In the present application, the graphene in the negative electrode active material and its mass content can be tested using instruments and methods known in the art. For example, a Raman spectrum can be obtained by a Raman spectrometer to characterize the graphene and the Raman peak loudness can be obtained to calculate the graphene mass content.
[0074] In some embodiments, the thickness of the silicon material layer is 5nm to 100nm, for example, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm and any value therebetween. It can be selected from 10nm to 80nm. When the thickness of the silicon material layer is within this range, the negative electrode active material has a better silicon content, which can improve its gram capacity, as well as better conductivity and cycle performance. Optionally, the thickness of the silicon material layer is 10nm to 80nm.
[0075] In some embodiments, the volume average particle size Dv50 of the silicon material in the silicon material layer is 2nm to 30nm, for example, 3nm, 5nm, 7nm, 9nm, 11nm, 13nm, 15nm, 17nm, 19nm, 21nm, 23nm, 25nm, 27nm, 29nm and any value therebetween. Optionally, the volume average particle size Dv50 of the silicon material in the silicon material layer is 3nm to 10nm.
[0076] The volume average particle size Dv50 of the silicon material in the silicon material layer has a well-known meaning in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be tested by instruments and methods well-known in the art. For example, it can refer to GB / T 19077-2016 particle size distribution laser diffraction method and be conveniently tested using a laser particle size analyzer, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0077] In some embodiments, the silicon material layer is connected to at least a portion of the surface of the MXene three-dimensional material through chemical bonds.
[0078] In some embodiments, the surface of the silicon material layer contains a first functional group, such as a hydroxyl functional group and / or a carboxyl functional group, and the surface of the MXene three-dimensional material contains a second functional group, such as a carboxyl functional group and / or a hydroxyl functional group. It should be noted that the first functional group and the second functional group are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.
[0079] In some embodiments, active carbon sites are formed on the surface of the MXene three-dimensional material, and the silicon material layer is connected to at least part of the surface of the MXene three-dimensional material through a silicon-carbon bond. Understandably, the above silicon-carbon bond is obtained by silicon bonding to the active carbon sites on the surface of the MXene three-dimensional material. The silicon material layer is connected to at least part of the surface of the MXene three-dimensional material through a silicon-carbon bond, which can make the silicon material layer on the surface of the negative electrode active material not easy to fall off, thereby enhancing the firmness of the silicon material layer to the MXene three-dimensional material, so as to better play the role of the MXene three-dimensional material in accommodating the volume changes of the silicon-based material.
[0080] In some embodiments, the volume average particle size Dv50 of the negative electrode active material is 5 μm to 20 μm, for example, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm and any value therebetween. Optionally, the volume average particle size Dv50 of the negative electrode active material is 8 μm to 15 μm.
[0081] The volume average particle size Dv50 of the negative electrode active material is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be tested by instruments and methods well known in the art. For example, it can be conveniently tested by a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0082] In some embodiments, the specific surface area of the negative electrode active material is 1 m 2 / g~50m 2 / g, for example 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g and any value therebetween. Optionally, the specific surface area of the negative electrode active material is 5m 2 / g~30m 2 / g.
[0083] In some embodiments, the mass content of silicon is 1% to 70%, based on the mass of the negative electrode active material, for example 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% and any value therebetween.
[0084] In some embodiments, based on the mass of the negative electrode active material, the mass content of the MXene material is 5% to 30%, for example, 10%, 15%, 20%, 25% and any value therebetween.
[0085] In the present application, a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) can be used to prepare the cross-section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then, EDX or EDS elemental analysis is combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test to obtain the element distribution map in the cross-section; combined with methods known in the art, the structure, composition and characteristics and content of each component of the negative electrode active material can be further obtained.
[0086] For example, the mass content of silicon and the mass content of MXene materials, a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) is used to prepare the cross-section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then the element distribution map in the cross section is obtained by EDX or EDS element analysis combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test; in an area within the cross section, the Si content in the area or the specific element content of the MXene material can be integrated. In order to improve the accuracy of the test, multiple areas (for example, 10) can be counted and the average value is taken as the test result.
[0087] For another example, the thickness of the silicon material layer can be measured by using a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) to prepare the cross section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then, the element distribution map in the cross section is obtained by EDX or EDS element analysis combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test; the thickness of the silicon material layer is obtained according to the element distribution of the cross section. More precisely, the thickness of the silicon material layer at multiple (more than 3, such as 8, 10, 12, etc.) different positions on the cross section can be tested, and the average value is recorded as the thickness of the silicon material layer.
[0088] Method for preparing negative electrode active material
[0089] A second aspect of the present application provides a method for preparing a negative electrode active material, comprising:
[0090] S10, providing MXene three-dimensional materials; and
[0091] S20, forming a silicon material layer on the MXene three-dimensional material.
[0092] In some embodiments, the method for preparing the MXene three-dimensional material comprises the following steps:
[0093] S11, mixing MXene material, graphene oxide, a dispersant and a reducing agent to obtain a mixed solution;
[0094] S12, subjecting the mixed solution to a hydrothermal reaction to obtain a MXene gel;
[0095] S13. Freeze-dry the MXene gel to obtain a MXene three-dimensional material.
[0096] Optionally, in step S11, the preparation method of MXene material includes: using a first etchant to etch and peel off the MAX material. It should be noted that the first etchant is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features. The first etchant is not particularly limited, and specific examples can be listed as follows: one or more of HF, LiF, NH4HF, HCl, H2SO4, NaOH and KOH. The general structural formula of MAX material is M 1 m+1 AX 1 m , where M 1 It includes at least one of Ti, Nb, V, Mo, Zr, Cr, W or Ta, A is a main group III or IV element, X 1 The MAX material includes at least one of C or N, and m is 1, 2 or 3. The MAX material is not particularly limited and can be selected according to the actual needs of the MXene material. Specific examples include: Ti2AlC, Ti3AlC2, Ta4AlC3, TiNbAlC, (V 0.5 Cr 0.5 )3AlC2, V2AlC, Nb2AlC, Nb4AlC3, Ti3AlCN, Ti3SiC2, Ti2SiC, Ta4SiC3, TiNbSiC, (V 0.5 Cr 0.5 )One or more of 3SiC2, V2SiC, Nb2SiC, Nb4SiC3 and Ti3SiCN.
[0097] Further optionally, the dispersant may be one or more of water, ethanol, methanol, acetone, and ethyl acetate.
[0098] Further optionally, the reducing agent can be HI, NaBH4, LiBH4, or hydrazine hydrate.
[0099] It should be noted that in step S11, the order of adding the MXene material, graphene oxide, dispersant and reducing agent when mixing is not particularly limited.
[0100] Optionally, the reaction temperature of the hydrothermal reaction in step S12 is 50° C. to 120° C., and the reaction time is 2 h to 6 h.
[0101] Optionally, the freeze-drying reaction temperature in step S13 is -100°C to -20°C, and the reaction time is 12h to 48h.
[0102] In some embodiments, step S11 further comprises: adding a second etchant to the mixed solution to etch and form the active carbon sites. Optionally, the second etchant is Ni2+ Salt. It should be noted that the second etchant is only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can it be understood as implicitly indicating the importance or quantity of the indicated technical features. The second etchant is not particularly limited, and specific examples can be listed as follows: NiCl2, Ni(NO3)2, CoCl2, Co(NO3)2. The purpose of adding the second etchant is to form defective carbon sites on the surface of the MXene three-dimensional material so that the silicon material layer can bond to the MXene three-dimensional material, making the combination of the two stronger.
[0103] In some embodiments, the weight ratio of the second etchant to the MXene material is 0.05 to 0.3, such as 0.1, 0.15, 0.2, 0.25, and any value therebetween. The weight ratio of the second etchant to the MXene material is within the above range, which can provide sufficient active defect sites for bonding between the silicon material layer and the MXene three-dimensional material.
[0104] In some embodiments, the mass content of the MXene material in the mixed solution is 30% to 97%, and can be optionally 40% to 80%, based on the total mass of the MXene material and graphene oxide. It should be noted that the MXene material self-assembles under the action of graphene oxide, and the mass content of the MXene material in the finally formed MXene gel is equal to the mass content of the MXene material in the mixed solution, and the mass content of graphene in the finally formed MXene gel is equal to the mass content of graphene oxide in the mixed solution.
[0105] In some embodiments, the method for forming the silicon material layer includes at least one of chemical vapor deposition, physical vapor deposition, plasma spraying and screen printing, and chemical vapor deposition may be selected.
[0106] Negative electrode
[0107] The third aspect of the embodiment of the present application provides a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the composite negative electrode material of the first aspect of the present application or the composite negative electrode material prepared by the method of the second aspect of the present application. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0108] The negative electrode plate includes the negative electrode active material provided in the present application, wherein the negative electrode active material can improve the cycle stability of the battery under high-rate rapid charging and discharging conditions.
[0109] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.
[0110] In some embodiments, the negative electrode active material does not exclude other negative electrode active materials other than the negative electrode active material provided in the present application. Other negative electrode active materials may adopt negative electrode active materials for secondary batteries known in the art. As an example, other negative electrode active materials may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, other silicon-based materials, tin-based materials, lithium titanate, etc. The other silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode active material layer is 70-100% by weight, based on the total weight of the negative electrode active material layer.
[0111] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode active material layer is 0-30% by weight, based on the total weight of the negative electrode active material layer.
[0112] In some embodiments, the negative electrode active material layer may further optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode active material layer is 0-20 weight %, based on the total weight of the negative electrode active material layer.
[0113] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode active material layer is 0-15 wt %, based on the total weight of the negative electrode active material layer.
[0114] In some embodiments, the negative electrode sheet can be prepared by the following method: the above components for preparing the negative electrode sheet, such as the negative electrode active material provided in the present application, optional other negative electrode active materials, optional binder, optional conductive agent and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The solid content of the negative electrode slurry can be 30-70wt%, the viscosity at room temperature can be adjusted to 2000-10000mPa·s, and the compaction density of the negative electrode sheet can be 1.2-2.0g / m 3 , the thickness of the negative electrode active material layer can be 34 μm to 143 μm.
[0115] The thickness T of the negative electrode active material layer can be measured by using a micrometer, for example, a Mitutoyo 293-100 micrometer with an accuracy of 0.1 μm. It should be noted that the thickness of the negative electrode active material layer described in this application refers to the thickness of the negative electrode active material layer in the negative electrode sheet after cold pressing and used to assemble the battery.
[0116] The negative electrode sheet of the present application does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode sheet of the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode sheet of the present application also includes a protective layer covering the surface of the negative electrode active material layer.
[0117] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0118] In one embodiment of the present application, a secondary battery is provided.
[0119] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0120] Positive electrode
[0121] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material of the first aspect of the present application.
[0122] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0123] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0124] In some of the embodiments, the positive electrode active material may adopt the positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode active material layer is 80-100% by weight, based on the total weight of the positive electrode active material layer.
[0125] In some embodiments, the positive electrode active material layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode active material layer is 0-20wt%, based on the total weight of the positive electrode active material layer.
[0126] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode active material layer is 0-20wt%, based on the total weight of the positive electrode active material layer.
[0127] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The positive electrode slurry has a solid content of 40-80wt%, the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the compacted density of the positive electrode sheet is 3.0-3.6g / cm 3 , optional: 3.3-3.5g / cm 3 The thickness of the positive electrode active material layer is 51-152 μm.
[0128] The thickness T of the positive electrode active material layer can be measured by using a micrometer, for example, a Mitutoyo 293-100 micrometer with an accuracy of 0.1 μm. It should be noted that the thickness of the positive electrode active material layer described in this application refers to the thickness of the positive electrode active material layer in the positive electrode sheet after cold pressing and used to assemble the battery.
[0129] Electrolytes
[0130] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0131] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0132] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate. The concentration of the electrolyte salt is generally 0.5-5 mol / L.
[0133] In some of the embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0134] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0135] Isolation film
[0136] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0137] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular limitation.
[0138] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0139] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0140] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.
[0141] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 5 The secondary battery 5 is a square structure as an example.
[0142] In some of these embodiments, reference Figure 6 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0143] In some of the embodiments, the secondary batteries may be assembled into a battery module. The number of the secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0144] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0145] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0146] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. The specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0147] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0148] In addition, the present application also provides an electrical device, which includes at least one of the secondary batteries, battery modules, or battery packs provided in the present application. The secondary batteries, battery modules, or battery packs can be used as power sources for electrical devices, and can also be used as energy storage units for electrical devices. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.
[0149] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0150] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0151] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0152] Example
[0153] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0154] 1. Preparation Example
[0155] Preparation Example 1
[0156] 1. 50 mL of 12 mol / L concentrated hydrochloric acid and 20 g of LiF were stirred and mixed in a polytetrafluoroethylene liner (hereinafter referred to as a hydrothermal reactor) at a stirring rate of 50 rad / min to obtain a mixed solution of HCl and LiF; the hydrothermal reactor was placed in an ice-water bath, 10 g of Ti3AlC2 raw material was weighed and added to the mixed solution of HCl and LiF in 5 times, each time with an interval of 20 minutes, and the temperature of the hydrothermal reactor should not be higher than 20°C. After the TiAlC raw material was added, it was placed in a water bath at 35°C and stirred for 24 hours for etching; the etched solution was centrifuged at 5000 r / min to retain the upper black solution; it was placed in an ultrasonic bath for 2 hours to obtain a well-exfoliated MXnen material, which was characterized as having a structural formula of Ti3C2 and surface functional groups including F, O, and OH.
[0157] 2. MXnen material and graphene oxide are dispersed in solvent water in a weight ratio of 7:3 and mixed evenly, and then an excess of HI reducing agent is added, and then NiCl2 etchant is added, the amount of NiCl2 etchant added is 10% of the weight of the MXnen material, and the mixed solution is placed in a hydrothermal kettle, sealed and transferred to an 80°C oven for low-temperature hydrothermal treatment for 24 hours to obtain a MXene hydrogel; the MXene hydrogel prepared above is immersed in an ethanol solution and fully soaked for 72 hours to remove the iodine attached to the surface, and rinsed with clean water until the pH of the cleaning solution is 7; the washed MXene hydrogel is placed in an 80°C oven and dried for 2 hours, then transferred to a freeze dryer, and freeze-dried at -30°C for 48 hours to obtain a MXene aerogel.
[0158] 3. Place the MXene aerogel in a tubular furnace to deposit a nano-silicon material layer, Ar inert gas, 900℃ for 2h, the reaction gas source is SiH4 and C2H2 with a volume ratio of 2:1, the flow rate is 50mL / min, the deposition temperature is 900℃, the deposition time is 30min, and the MXene material with amorphous silicon deposition is obtained, which is the negative electrode active material.
[0159] According to SEM scanning electron microscopy testing, the negative electrode active material has a three-dimensional network structure and a three-dimensional network skeleton.
[0160] Preparation Examples 2 to 26
[0161] The preparation methods of Preparation Examples 2 to 26 are similar to Preparation Example 1. The difference is that the negative electrode active material and related parameters in the preparation process are adjusted. The specific parameters are shown in Table 1 below. Among them, "-" means that the corresponding parameter does not exist.
[0162] Preparation Comparative Example 1
[0163] The preparation method of Comparative Example 1 is similar to that of Example 1. The difference is that the deposition of the nano-silicon material layer in step 3 is replaced by mechanical mixing of the MXene aerogel and nano-silicon particles obtained in step 2, and the mass of the nano-silicon particles is the same as the mass of the silicon material layer in Example 1, that is, the silicon content and the content of the MXene material in the final negative electrode active material are the same as those in Example 1.
[0164] 2. Application Examples
[0165] Example 1
[0166] 1) Preparation of positive electrode
[0167] The cathode active material ternary material nickel cobalt manganese (NCM811), conductive carbon black SP and binder PVDF were dispersed in the solvent NMP according to a weight ratio of 97:2:1 and mixed evenly to obtain a cathode slurry; the cathode slurry was evenly coated on the cathode current collector aluminum foil, and then dried, cold pressed, die-cut and striped to obtain a cathode electrode sheet, and the coating amount per unit area was 0.27g / 1540.25mm 2 .
[0168] 2) Preparation of negative electrode sheet
[0169] The negative electrode active material prepared in Example 1, conductive carbon, thickener sodium hydroxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a weight ratio of 96:2:1:1, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was evenly coated on a copper foil; the copper foil was dried at room temperature and then transferred to an oven at 85°C for drying, and then supercooled pressed and cut to obtain a negative electrode sheet, the coating amount per unit area of which was 0.17 g / 1540.25 mm 2 .
[0170] 3) Isolation film
[0171] A 12 μm thick porous isolation membrane was selected.
[0172] The preparation of the porous isolation membrane includes: using a polyethylene microporous film as a porous isolation membrane substrate, mixing inorganic alumina powder, polyvinylpyrrolidone, and acetone solvent in a weight ratio of 3:1.5:5.5 to form a slurry, coating it on one side of the substrate, and drying it to obtain a porous isolation membrane.
[0173] 4) Preparation of electrolyte
[0174] The organic solvent is a mixed liquid containing ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, wherein the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:2:1. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.
[0175] 5) Preparation of batteries
[0176] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound into a square bare battery cell, loaded with aluminum plastic film, and then baked at 100°C to remove water, 320g of the corresponding electrolyte is injected, and the mouth is sealed. After standing, hot and cold pressing, formation, clamping, and capacity division, a finished battery with a capacity of 180Ah is obtained. The battery is charged for the first time. N / P = negative electrode gram capacity * negative electrode active material mass / positive electrode gram capacity * positive electrode active material mass
[0177] The secondary batteries of Examples 2 to 26 and the secondary battery of Comparative Example 1 were prepared in a similar manner to the secondary battery of Example 1, but the negative electrode active materials of the corresponding preparation examples were used.
[0178] 3. Test Method
[0179] 1. Specific surface area and mesoporosity test
[0180] The specific surface area and pore size distribution of the negative electrode active materials, MXene aerogels and other materials in the examples and comparative examples were measured by nitrogen adsorption / desorption method using a specific surface area analyzer (TristarII 3020M). The specific test was carried out in accordance with the national standard GB / T 19587-2017.
[0181] 2. Particle size distribution test
[0182] The particle size distribution of the negative electrode active material and the silicon material of the silicon material layer in the embodiment and the comparative example was tested using a Malvern particle size tester to obtain the average volume particle size Dv50 of the negative electrode active material and the silicon material of the silicon material layer, wherein the specific test was performed in accordance with the national standard GB / T19077-2016.
[0183] 3. Number of MXene flakes, flake diameter, flake thickness and interlamellar spacing:
[0184] The tapping mode of the atomic force microscope is used to observe the number of MXene flakes, and the flake diameter, flake thickness and interlamellar spacing of the MXene are tested with the ruler carried by the atomic force microscope. Since the shape of MXene is usually irregular, a line is drawn between the two points on the MXene surface with the longest distance, and a perpendicular bisector of the line is drawn. The average length of the MXene flake in the above two directions is taken as the MXene flake diameter. Figure 1 As shown, the diameter of the MXene sheet is D = (l1 + l2) / 2. The number of MXene samples should be no less than 100. The diameter of the MXene sheet is the average diameter of the above MXene samples.
[0185] 4. MXene aerogel density test
[0186] Place a certain amount of MXene aerogel in a special compaction mold, place the mold on a compaction (mass) density meter, set different pressures, and read the thickness of the carbon aerogel material powder under different pressures on the device. Calculate the density using the formula density = mass / volume.
[0187] 5. Silicon material layer thickness
[0188] A cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) is used to prepare the cross-section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then the element distribution map in the cross-section is obtained by surface scanning test using the X-Max EDS of the Oxford Instruments Group of the United Kingdom combined with the Sigma-02-33 SEM of the ZEISS of Germany, and the thickness of the silicon material layer is tested according to the element distribution of the cross-section. The thickness values of the silicon material layer at three different positions on the cross-section are taken, and the average value is recorded as the thickness of the silicon material layer.
[0189] 6. Test of the mass content of silicon in negative electrode active materials and the mass content of MXene materials
[0190] A cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) is used to prepare the cross-section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then the element distribution map in the cross-section is obtained by surface scanning test using the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of the ZEISS in Germany. In a region within the cross-section, the Si content in the region or the specific element content of the MXene material (such as Ti) is integrated. A total of 10 regions were counted in the test, and the average value was taken as the test result.
[0191] 7. Lithium-ion battery energy density and cycle life test
[0192] The cycle test temperature is 25°C. The battery is charged at a constant current of 3C to the upper limit voltage, and then charged at a constant voltage to 0.05C. After standing for 5 minutes, it is discharged at 0.33C to the lower limit voltage. The capacity obtained in this step is the initial capacity. The capacity is multiplied by the average discharge voltage and then divided by the cell volume to obtain the energy density. A 3C charge / 0.33C discharge cycle test is performed until the capacity decays to 80% SOH, and the corresponding number of cycles is recorded to obtain the corresponding life data.
[0193] 8. Battery expansion force test
[0194] Before test 7, the battery is fixed in the clamp of the pressure sensor and clamped with a fixed pressure. Capacity calibration and cycle testing are performed according to the process in test 7. The expansion force change is monitored during the cycle. The ratio of the expansion force increment when the capacity decays to 80% to the initial expansion force is the expansion force change.
[0195] Table 2 shows the negative electrode active materials and battery performance test results of Examples 1 to 26 and Comparative Example 1.
[0196] Table 1
[0197]
[0198]
[0199] Table 2
[0200]
[0201]
[0202] By comparing the examples and comparative examples, it can be seen that the negative electrode active material obtained by setting a silicon material layer on the surface of the MXene three-dimensional material with a three-dimensional network skeleton can reduce the expansion force of the battery and improve the energy density and cycle life of the lithium-ion battery at high rates. By controlling the relevant condition parameters in the preparation process of the negative electrode active material, the various properties of the negative electrode sheet and the lithium-ion battery can be adjusted, so that a lithium-ion battery with better comprehensive performance can be obtained according to actual application requirements.
[0203] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode active material, characterized in that: include: A MXene three-dimensional material having a three-dimensional network skeleton and a silicon material layer disposed on at least a portion of the surface of the MXene three-dimensional material, wherein the MXene three-dimensional material comprises a MXene material having a general structural formula of M n+1 X n , wherein M includes at least one of Ti, Nb, V, Mo, Zr, Cr, W and Ta; X includes at least one of C and N; and n is 1, 2 or 3.
2. The negative electrode active material according to claim 1, characterized in that The MXene includes one or more of Ti2C and Ti3C2.
3. The negative electrode active material according to claim 1 or 2, characterized in that: The MXene material satisfies at least one of the following characteristics (1) to (3): (1) The diameter of MXene flakes is 2 to 10 μm; (2) The number of MXene layers ranges from 1 to 5; (3) The thickness of MXene flakes is 1nm to 10nm.
4. The negative electrode active material according to claim 1, characterized in that The MXene three-dimensional material satisfies at least one of the following characteristics (4) to (5): (4) The mesoporosity of MXene three-dimensional materials is 30% to 70%; (5) The density of MXene three-dimensional materials is 10 mg / cm 3 ~60mg / cm 3 .
5. The negative electrode active material according to claim 4, characterized in that The MXene three-dimensional material is a MXene aerogel; Optionally, the MXene aerogel further comprises graphene; Optionally, based on the total mass of the MXene aerogel, the mass content of the graphene is 3% to 70%, and further optionally 20% to 60%.
6. The negative electrode active material according to claim 1, characterized in that The thickness of the silicon material layer is 5 nm to 100 nm, and can be optionally 10 nm to 80 nm.
7. The negative electrode active material according to claim 1, characterized in that The average volume particle size Dv50 of the silicon material in the silicon material layer is 2nm to 30nm, and can be optionally 3nm to 10nm.
8. The negative electrode active material according to claim 1, characterized in that The silicon material layer is connected to at least part of the surface of the MXene three-dimensional material through chemical bonds. Optionally, active carbon sites are formed on the surface of the MXene three-dimensional material, and the silicon material layer is connected to at least part of the surface of the MXene three-dimensional material by bonding with the active carbon sites.
9. The negative electrode active material according to any one of claims 1 to 8, characterized in that: The negative electrode active material satisfies at least one of the following characteristics (6) to (9): (6) The average volume particle size Dv50 is 5 μm to 20 μm; (7) Specific surface area is 1m 2 / g~30m 2 / g; (8) Based on the mass of the negative electrode active material, the mass content of silicon is 1% to 70%; (9) Based on the mass of the negative electrode active material, the mass content of the MXene material is 30% to 99%.
10. A method for preparing a negative electrode active material according to any one of claims 1 to 9, characterized in that: include: Providing the MXene three-dimensional material; The silicon material layer is formed on the MXene three-dimensional material.
11. The method for preparing the negative electrode active material according to claim 10, characterized in that: The preparation method of the MXene three-dimensional material comprises the following steps: S11, mixing the MXene material, graphene oxide, a dispersant and a reducing agent to obtain a mixed solution; S12, subjecting the mixed solution to a hydrothermal reaction to obtain a MXene gel; S13, freeze-drying the MXene gel to obtain a MXene three-dimensional material.
12. The method for preparing the negative electrode active material according to claim 11, characterized in that: Step S11 further includes: adding a second etchant to the mixed solution to etch and form the active carbon sites. Optionally, the etchant is Ni 2+ Salt.
13. The method for preparing the negative electrode active material according to claim 12, characterized in that: The weight ratio of the second etchant to the MXene material is 0.05 to 0.
3.
14. The method for preparing a negative electrode active material according to any one of claims 10 to 13, characterized in that: The method for forming the silicon material layer includes at least one of chemical vapor deposition, physical vapor deposition, plasma spraying and screen printing, and chemical vapor deposition can be selected.
15. A negative electrode plate, characterized in that: The invention comprises the negative electrode active material according to any one of claims 1 to 9 or the negative electrode active material prepared according to the method according to any one of claims 10 to 14.
16. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 15.
17. An electrical device, characterized in that: Comprising at least one of the secondary batteries described in claim 16.
Citation Information
Patent Citations
MXene-silicon composite negative electrode material, battery containing MXene-silicon composite negative electrode material, and preparation method and application of MXene-silicon composite negative electrode material
CN113066965A
Composite negative electrode material and preparation method thereof
CN113823781A
High-performance silicon-carbon composite material, preparation method thereof and lithium ion battery
CN114335527A
Negative active material, preparation method and application thereof
CN116190586A
Negative electrode active material, preparation method therefor, and secondary battery and apparatus related thereto
WO2023124913A1